Effect of human capital development on agribusiness performance among smallholder rice farmers in Ogun State - Brimah, Aminu Nassir; Yusuf, Ismaila; Abolade, Ayobami Paul (Journal of Asian Business Strategy, 2025)
Human capital development is critical for enhancing agribusiness performance, particularly in developing economies where agriculture is a key component of economic activity. Despite numerous capacity-building initiatives aimed at supporting agribusiness growth, agribusinesses still struggle with inadequate skills, training, and continuous learning, which hinder employment generation. This study examines the effect of human capital development on agribusiness performance in Ogun State. A quantitative research method was adopted, utilizing a survey design with a population of 37,200 agribusiness farmers. A sample size of 380 was selected using probability sampling techniques. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), and regression analysis was conducted to test the hypotheses. The results revealed a positive, significant relationship between human capital development and agribusiness employment generation, with an R² value of 0.26 indicating a moderate effect on agribusiness performance. The findings establish that continuous learning, adequate skill acquisition programs, and effective training collaborations will lead to employment generation. The study concluded that employment generation in agribusiness is possible through investment in continuous learning, skill acquisition, and training. The study recommended that agribusiness stakeholders should collaborate to implement specialized training programs that promote modern agribusiness practices, thereby enhancing employment generation and sustainability.